(untitled) - Bridges, Linda (Hoboken, N.J., 2007)
Strictly Right paints an intimate and penetrating portrait of the elegant and multifaceted figure who has helped to add a new dimension to the American political canvas
Keywords: Journalists,Chân dung nhà báo; United States